Lactate dehydrogenase in the guppy fish (Poecilia reticulata) as a biomarker of heavy-metal pollution in freshwater ecosystems - Yap, Chee Kong; Chong, Chou Min; Tan, Soon Guan (Universiti Malaysia Terengganu, 2011)
Heavy metal concentrations and allozyme variations were determined in females of guppy fish (Poecilia reticulata) populations collected from polluted and unpolluted sites. the concentrations of Cu and Fe were significantly (P<0.05) higher in guppies collected from polluted drainage compared to the unpolluted population. Higher concentrations of Cu, Fe and Zn (P<0.05)were found in the surface sediment, indicating contamination by the three metals in the polluted drainage. The insignificant difference (P>0.05) in the Zn concentrations between the polluted and the unpolluted populations indicated that Zn, as a major essential metal, was regulated in this freshwater fish. seven enzyme systems EST, G6PDH, LDH, MDH, PGI, PGM, and SDH were tested. Only LDH (lactate dehydrogenase) was found to be agood biomarker for the contamination of Cu and Fe in P. reticulata. The zymogram of teh unpolluted wild population showed the same monomorphic allele as the unpolluted domesticated guppies from a pet shop,thus, further confirming LDH in P. reticulata as agood biomarker of contamination by Cu.